Concerning Marya Schechtman's narrative account - Simuja, Clement (Rhodes University, Faculty of Humanities, Department of Philosophy)
The persistence of personal identity stands at the heart of many human practices, such as paying individuals for their work or holding people responsible for their actions. As such, it seems important that theories of personal identity are able to account for the practical implications of continuity of personal identity. Mindful of the practical importance of personal identity, Marya Schechtman (1994) argues that her narrative view only accounts for the four features that persons must possess. Any account of personal identity is supposed to make persons capable of possessing these features. She then posits her narrative self-constitution view as an account of personal identity she feels is capable of explaining the link between personal identity and certain features of persons. In this thesis project, I present how the narrative views, as described by Schechtman and others, are interpretive enterprises and that this leads them to a potentially devastating conclusion. The narratives must be constructed from something, and I argue that it is memory. But empirical facts about memory do not allow for it to persist in a quantitative way, but rather in a qualitative way, much like persons. Upon making this argument, I further argue that if mainstream psychological views is correct, this reduces the persistence of memory to resemblance relations. And memory is the building blocks of narrative. If this is the case, then narrative is also reduced to resemblance relations. Narrative, therefore, does not persist through time in a non-qualitative way, and one is better off accepting a psychological theory by virtue of parsimony. Ultimately, I argue that Schechtman and narrative theorists may save narrative views by adopting what I call as a 'causal narrative view'. A causal narrative view will encapsulate all of the relevant features of the typical narrative view, including the emphasis on construction, but will also add the addendum that narrative states must be placed in a causal relation to each other.
Keywords: Schechtman, Marya, 1960- -- Criticism and interpretation; Narrative inquiry (Research method); Identity (Psychology); Identity (Philosophical concept); Self; Individuality